2016
DOI: 10.11609/jott.2340.8.9.9155-9170
|View full text |Cite
|
Sign up to set email alerts
|

Pollination ecology and fruiting behavior of Pavetta indica L. (Rubiaceae), a keystone shrub species in the southern Eastern Ghats forest, Andhra Pradesh, India

Abstract: C omm u n fi c a ft fi o n P o fl fl fi n a ft fi o n e c o fl o g y a n d f r u fi ft fi n g b e h a v fi o r o f P a v e ft ft a fi n d fi c a L . ( R u b fi a c e a e ) , a k e y s ft o n e s h r u b s p e c fi e s fi n ft h e s o u ft h e r n E a s ft e r n G h a ft s f o r e s ft , A n d h r a P r a d e s h , I n d fi a A . J . S o fl om o n R a j u , M . M a fl fl fi k a r j u n a R a o , K . V e n k a ft a R am a n a , C . P r a s a d a R a o & M . S u fl a k s h a n a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
7
1
1
Order By: Relevance
“…A particular pollinator functional group can be thought of as part of the plant's fundamental niche (Johnson, 2010). Several studies have reported plants of various groups with SPP and long floral tube being visited by generalized pollinators, despite the expectation that they would be exclusively pollinated by long‐tongued pollinators (Vaughton, 1996; Lin et al, 2012; Raju & Rao, 2016; Raju et al, 2016). Most of them speculated that short‐proboscis insects collecting pollen on SPP flowers were ineffective pollinators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A particular pollinator functional group can be thought of as part of the plant's fundamental niche (Johnson, 2010). Several studies have reported plants of various groups with SPP and long floral tube being visited by generalized pollinators, despite the expectation that they would be exclusively pollinated by long‐tongued pollinators (Vaughton, 1996; Lin et al, 2012; Raju & Rao, 2016; Raju et al, 2016). Most of them speculated that short‐proboscis insects collecting pollen on SPP flowers were ineffective pollinators.…”
Section: Introductionmentioning
confidence: 99%
“…ex Sm. and Pavetta indica L. fed on pollen, and were thought to inadvertently pollinate the flowers, even though they can carry more pollen grains than butterflies and hawkmoths (Raju & Rao, 2016; Raju et al, 2016). Nevertheless, the reasons mentioned above are inadequate to exclude short‐tongued insects as pollinators.…”
Section: Introductionmentioning
confidence: 99%
“…Por apresentar grande número de espécies nos sub-bosques das florestas tropicais, a família exerce influência na estrutura da vegetação (Gentry & Emmons 1987, Lopes & Buzato 2005. Além disso, possui papel importante como fonte de recursos para a fauna que se alimenta de pólen, néctar e frutos (Mesquita-Neto et al 2015, Faria & Araujo 2016, Raju & Rao 2016, Mesquita-Neto et al 2018, revelando a importância de estudar a fenologia das espécies de Rubiaceae nesse bioma e ressaltando que é primordial na busca da compreensão do funcionamento destes ecossistemas.…”
Section: Introductionunclassified
“…In the genus Uncaria, male reproductive organs are known to mature before female reproductive organs (i.e., protandry; Raju & Rao, 2016). Uncaria rhynchophylla presents its pollen to vectors on structures other than anthers and in this case the pollen grains are attached to immature stylar heads; a phenomenon referred to as secondary pollen presentation (Fig.…”
mentioning
confidence: 99%
“…Uncaria rhynchophylla presents its pollen to vectors on structures other than anthers and in this case the pollen grains are attached to immature stylar heads; a phenomenon referred to as secondary pollen presentation (Fig. 1B;Raju & Rao, 2016). The styles of U. rhynchophylla are exerted from corolla tubes ( Fig.…”
mentioning
confidence: 99%